Income growth and preferences for redistribution: The role of absolute and relative economic experiences - David Weisstanner (Luxembourg Income Study (LIS), 2020)
The unequal distribution of economic gains is a prominent factor behind policy preferences and recent electoral outcomes, but often fails to explain trends in preferences over time. This study introduces the distinction between "absolute" and "relative" economic experiences and explore how they shape preferences for redistribution. I argue that absolute and relative experiences have offsetting effects on redistribution preferences. Contrary to political economy theories, I expect that lower absolute income growth reduces demand for redistribution, because only favourable absolute economic contexts that are widely shared create the willingness to finance costly redistributive policies. Support for this expectation is provided in an empirical analysis that combines novel estimates for absolute and relative income growth with longitudinal survey data on redistribution preferences in 20 advanced democracies between 1985 and 2019. The distinction between absolute and relative economic experiences carries broader implications for research in political economy and comparative politics.
Keywords: 330; comparative politics; preferences for redistribution; income growth; absolute and relative economic experiences